The Effect of Job Burnout And Financial Compensation on Employee Performance (Study on Lestari Baru Gemolong) - Yuniyar Hazhiyah; Kusdiyanto Kusdiyanto (IQTISHADequity jurnal MANAJEMEN, 2023)
This study intends to analyse the impact of financial compensation and job burnout on employee performance. Job Burnout and Financial Compensation are the independent variables used in this study. While Employee Performance is the dependent variable of this study. In this survey, employees of Lestari Baru Gemolong in Sragen Regency were sampled with a total of 60 respondents. This research technique is quantitative and uses survey distribution to obtain primary data. Multiple linear regression analysis is the technique used for analysis. Data processing in this study used SPSS version 26 software. According to the research findings, employee performance at Lestari Baru Gemolong is significantly influenced by job burnout and monetary remuneration.